Hi All, This reads as one over sec theta + tan theta = sec theta - tan theta = cos theta over one + sin theta 1 / secѳ + tanѳ = sec ѳ – tanѳ = cosѳ / 1 + sinѳ My job is to prove the identities
Any help would be appreciated
Hi All, This reads as one over sec theta + tan theta = sec theta - tan theta = cos theta over one + sin theta 1 / secѳ + tanѳ = sec ѳ – tanѳ = cosѳ / 1 + sinѳ My job is to prove the identities
Any help would be appreciated
Please either use LaTeX or brackets, so that we know what you are talking about...
Hi All, This reads as one over sec theta + tan theta = sec theta - tan theta = cos theta over one + sin theta 1 / secѳ + tanѳ = sec ѳ – tanѳ = cosѳ / 1 + sinѳ My job is to prove the identities
Any help would be appreciated